The Women in Top Management : The Case Study of EY company - Tomčovčíková, Michaela; Křečková Kroupová, Zuzana, 1972-; Volfová, Jitka, 1982-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
The thesis analyses the course and tempo of women´s careers in comparison with those of men, based on an analysis of my own research conducted at the company EY. The results of the research demonstrates, whether it is more challenging for women or men to achieve a managerial position. The thesis identifies and analyse the different factors that may influence the career of women, based on the theoretical findings and on a qualitative interview.
Vedoucí práce: Zuzana Křečková Kroupová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses